User-Centred Subtitling: Usability as an Assessment and Process Framework for Interlingual Subtitles - Tuominen, Tiina (European Association for Studies in Screen Translation, 2026)
The audience’s perspective is often prominent in evaluating subtitle quality, with concepts such as readability being used as assessment criteria. In audiovisual translation research, reception studies have become a visible presence. Understanding the audience is thus clearly central for both research and practice, but information on actual audience preferences does not always filter through to subtitling practice or to quality assessment. Therefore, there seems to be a need for a model that could support the existing audience orientation and make the audience’s perspective a consistent consideration throughout the subtitling process. This article proposes the concept of usability as a framework for an audience-oriented view of interlingual subtitling. The article introduces the usability-based user-centred translation (UCT) model and discusses how it could be applied to subtitling practice. In addition, it explores the differences and similarities between UCT and existing practices in the media localisation industry. This comparison aims to demonstrate how UCT could be implemented in the industry, what added benefit it might bring in comparison to current practices, and how it could fit into existing workflows.